Service innovation implementation: a systematic review and research agenda - Singh, Shiwangi; Akbani, Ismail; Dhir, Sanjay (The Service industries journal, 2020)
This study presents a systematic literature review on the implementation of service innovation in the extant literature. This study conducts a comprehensive review of published articles in the extant literature related to various aspects of service innovation implementation and then critically reviews the extant literature to identify major factors that affect the success of innovation implementation. Research gaps have thus been identified through the lens of theory development, context, characteristics, and methodology (TCCM framework). This article analyzes underexplored areas of research theme in the domain of service innovation implementation, thereby providing directions for future research.